EVOLVING CERVICAL CANCER SCREENING GUIDELINES AND HPV VACCINATION STATUS. A LITERATURE REVIEW - Zuzanna Tomaszewska; Adrianna Perzanowska; Anna Zielińska; Agata Nowacka; Julia Ciechanowicz; Stanisław Ciechanowicz; Julia Dura; Marika Gutowska; Piotr Kupidłowski; Aleksandra Przybylska (International Journal of Innovative Technologies in Social Science, 2025)
Background: Persistent infection with high-risk types of human papillomavirus is the primary cause of cervical cancer globally. Recent decades have witnessed significant advances in prevention, with the introduction of effective prophylactic HPV vaccines and highly sensitive molecular screening methods transforming how cervical cancer is detected and managed. Aim of this review is to explore the impact of HPV vaccination programs on cervical cancer prevention strategies, focusing on how vaccination coverage influences the global shift from traditional cytology-based screening to HPV DNA testing in selected high-income countries. Methodology: A comprehensive search was conducted across scientific databases, including PubMed, the Cochrane Library, and WHO reports, focusing on recent peer-reviewed studies. Results: The diagnostic performance of cytology has declined in vaccinated populations due to fewer abnormal findings, prompting a shift toward primary HPV DNA testing. This method offers sensitivity rates exceeding 90% and supports longer screening intervals of five years or more. Countries like Australia, the Netherlands, Sweden, and the UK have adopted nationwide HPV-based screening, while Poland initiated pilot HPV testing programs in 2024. However, several barriers persist, including disparities in vaccine distribution, the high cost of molecular diagnostics, and persistent public hesitancy toward vaccination. Conclusions: Combining widespread HPV vaccination with HPV DNA-based screening offers the most promising strategy for reducing cervical cancer incidence and achieving the WHO’s 2030 elimination targets. Those recommendations include expanding gender-neutral vaccination, supporting transitions to HPV testing in lagging regions, and incorporating innovations like self-sampling to improve outreach and screening participation.